2016
DOI: 10.1038/ejhg.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

Association of the IGF1 gene with fasting insulin levels

Abstract: Targeted resequencing of DNA at specific genes or other genomic loci is now feasible for hundreds or thousands of samples, and costs for larger-scale resequencing are decreasing rapidly. For at least the AMS 2000 subject classifications: Primary 62D05, 62P10; secondary 62J12 Keywords and phrases: case-cohort design, case-control design, sampling weights 1 2 T. LUMLEY ET AL.next few years, resequencing will need to be confined to small subsets of the large samples on which genome-wide association studies have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Similarly, Mannino et al also suggested that subjects carrying with the GG genotype of rs35767 showed lower insulin sensitivity and IGF-1 concentration compared with those carrying the A allele (Mannino et al 2013 ). The parameters of the rs5742694 polymorphism were reported for the first time as carriers of the TT genotype showing higher insulin sensitivity and lower insulin secretion (Willems et al 2016 ). However, no significant correlation was found between the rs5742694 polymorphism and IGF-1 level in serum.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Mannino et al also suggested that subjects carrying with the GG genotype of rs35767 showed lower insulin sensitivity and IGF-1 concentration compared with those carrying the A allele (Mannino et al 2013 ). The parameters of the rs5742694 polymorphism were reported for the first time as carriers of the TT genotype showing higher insulin sensitivity and lower insulin secretion (Willems et al 2016 ). However, no significant correlation was found between the rs5742694 polymorphism and IGF-1 level in serum.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Huyghe et al also identified low-frequency coding variants associated with FPI at SGM2 and MADD gene in Finnish males [17]. Moreover, it is suggested that IGF-1 genetic variants were associated with FI in European ancestry [18]. Manning et al also observed that 6 SNPs in COBLL1-GRB14, IRS1, PPP1R3B, PDGFC, UHRF1BP1, and LYPLAL1 are correlated with the FI level [19].…”
Section: Discussionmentioning
confidence: 99%
“…The first hypothesis is that these SNPs might tag other variants in the IGF1 gene associated with insulin sensitivity and β cell function. In a recent study, the investigators revealed plenty of rare variants associated with fasting insulin levels that had not been previously described, by further study of the IGF1 gene [ 26 ]. Examination showed that the variants were located near the DNAseI hypersensitive sites and FOXA1 binding sites, indicating that they might have direct function because FOXA1 is a major transcriptional regulator factor in glucose homeostasis and insulin metabolism [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%